Preparation process of additive for large-temperature-difference high-salt-resistance oil well cement
By using zinc-aluminum hydrotalcite calcined product to adsorb retarder, the problem of easy decomposition and poor salt resistance of oil well cement at high temperature is solved, and the high compressive strength and salt resistance of cement are achieved, which is suitable for deep marine oil fields. cementing demand.
Patent Information
- Application Number
- CN202411813129.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The cement admixtures of existing oil wells are prone to decomposition under high temperature conditions, resulting in slow development of compressive strength of cement stones in the top low temperature section and poor salt resistance, which cannot effectively meet the cementing needs of cement in deep-seated ocean oil fields.
Zinc-aluminum hydrotalcite calcined product as a support, combining 2-acrylamide-2-methylpropanesulfonic acid, 3-propane-2-enoyloxypropane-1-sulfonate, carboxylic acid monomers and acrylamide Prepare retarders for monomer-like materials, and use dynamic crystallization and ultrasonic dispersion technology to make large temperature difference high-resistance salt-resistant oil well cement adsorb retarders to improve the water-resistance and resistance of cement. Pressure strength.
This process simplifies the preparation process, improves the compressive strength and salt resistance of cement, can slow release of retarder at high temperature, avoid abnormal thickening and super-retarding in early hydration, and is suitable for large temperature differences and high temperature environments. .
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of admixtures for oil fields, and in particular relates to a preparation process of an admixture for large temperature difference and high salt resistance oil well cement. Background Art
[0002] Oil well cement is cement specially used for cementing oil and gas wells. It is an important factor affecting the quality of cementing. Cement slurry needs to be injected into the well. Therefore, oil well cement is required to have suitable density and fluidity, be able to solidify and reach a high early compressive strength in a short time, and the hardened cement slurry has good stability and corrosion resistance. In order to make the various properties of cement better meet the requirements of cementing, it is often necessary to add one or more admixtures to the cement slurry system to adjust its performance. In recent years, with the increasing depletion of oil and natural gas resources in shallow waters, my country's oil production has gradually developed towards deep and ultra-deep layers in the ocean. Due to the high temperature conditions underground, especially when the temperature exceeds 200°C, the hydration and hardening process of oil well cement, the composition of hydration products, and the microstructure of the hardened body will all undergo significant changes, affecting the cement slurry thickening and cement stone strength.
[0003] Under high temperature conditions, the concentration of free calcium ions in the early stage of cement hydration is relatively low. The retarder molecules compete for calcium ions and multiple polymer molecules chelate one calcium ion, which makes the long-chain polymers form a bridge network, which is easy to cause overlap between the long-chain molecules of the retarder in the slurry, resulting in some non-chelated polymer molecules being entrained in the polymer of the bridge network. Under the mechanical rotation of the stirring shaft, the bridge network and the overlapping retarder carried by it are stirred around the outside of the stirring shaft, resulting in a decrease in the distribution of the retarder in the core, and the hydration process of the cement slurry cannot be effectively inhibited, inducing abnormal thickening problems. In addition, the existing high-temperature retarders need to ensure the safe construction of cement slurry at ultra-high temperatures, while also causing the slow development of the compressive strength of the cement stone in the top low-temperature section, that is, over-retardation. Therefore, it is necessary to develop large temperature difference anti-salt admixtures to make the performance of oilfield cement meet the cementing requirements.
[0004] Patent CN114395074B discloses a preparation method and application of an organic-inorganic hybrid fluid loss additive for oil well cement. The preparation method comprises the following steps: adding 2-acrylamide-2-methylpropanesulfonic acid, acrylamide monomers, carboxylic acid monomers and sodium p-styrene sulfonate to distilled water, stirring evenly at room temperature, and adjusting the pH; adding an initiator, heating the reaction to obtain a liquid anionic polymer fluid loss additive; mixing the liquid anionic polymer fluid loss additive with magnesium-aluminum hydrotalcite, stirring at 65-75°C for 6-8 hours for sedimentation, washing with water, centrifuging, freeze-drying and grinding to obtain an organic-inorganic hybrid fluid loss additive for oil well cement. This invention uses water as the dispersion medium, has a simple preparation process and low cost, can effectively reduce the water loss of cement slurry at high temperature, improve the over-retardation phenomenon of cement slurry caused by a single polymer fluid loss reducer, has good adaptability to oil well cement, and is suitable for use as an oil well cement fluid loss reducer. However, the use of this invention at higher temperatures is limited by the thermal stability of the fluid loss reducer, and the high temperature difference salt resistance performance is not achieved by improving the structure and composition of hydrotalcite. Summary of the invention
[0005] The purpose of the present invention is to provide a process for preparing an admixture for oil well cement with large temperature difference and high salt resistance, so as to solve the technical problems in the prior art that traditional oilfield cement admixtures are easy to decompose at high temperature, the compressive strength of cement stone in the top low temperature section develops slowly and the salt resistance is poor.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The preparation process of an admixture for large temperature difference and high salt resistance oil well cement comprises the following steps: S1, adding zinc source and aluminum source to a mixed solution of sodium hydroxide and sodium carbonate, adjusting the pH of the solution to 9.5±0.5, and dynamically crystallizing at 70~90°C for 6~10h to obtain a ZnAl-CO3-LDH precursor; S2, calcining the ZnAl-CO3-LDH precursor at low temperature to obtain a zinc-aluminum hydrotalcite calcined product; S3. Add the retarder into deionized water, introduce nitrogen and disperse ultrasonically, add the calcined product of zinc-aluminum hydrotalcite into the retarder solution for reaction, stir continuously during the reaction, and after the reaction is completed, cool naturally and wash with water until neutral, and dry at 60°C to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
[0007] Preferably, the preparation method of the above-mentioned retarder is as follows: S11, adding 2-acrylamide-2-methylpropanesulfonic acid, sodium 3-prop-2-enoyloxypropane-1-sulfonate, and carboxylic acid monomers into deionized water, stirring at room temperature until the three monomers are completely dissolved, and then pouring into a four-necked flask; S12, adding sodium hydroxide solution dropwise to the solution, adjusting the pH value of the solution to 5-6, adding acrylamide monomer and chelating agent, stirring evenly and pouring into a four-necked flask; S13, when the temperature reaches 60°C, add an initiator dropwise into the four-necked flask, react at 60-65°C for 0.5-1h, then raise the temperature to 70-75°C for 2.5-3h, and collect the liquid retarder after the reaction is completed; The solid system comprises 2-acrylamide-2-methylpropane sulfonic acid, sodium 3-prop-2-enoyloxypropane-1-sulfonate, carboxylic acid monomers, acrylamide monomers, a chelating agent and an initiator.
[0008] Preferably, the carboxylic acid monomer in S11 is one or more of itaconic acid, acrylic acid, maleic anhydride, and cis-2-methyl-2-butenedioic acid.
[0009] Preferably, the acrylamide monomer in S12 is one or more of N,N-dimethylacrylamide and acrylamide.
[0010] Preferably, the chelating agent in S12 is one or more of ethylenediaminetetraacetic acid and sodium pyrophosphate.
[0011] Preferably, the mass of the chelating agent added in S12 is 0.24-0.3% of the total mass of the added solids and water.
[0012] Preferably, the initiator in S13 is one or more of ammonium persulfate and azobisisobutyronitrile.
[0013] Preferably, the amount of initiator added in S13 is 1.4-1.6% of the mass of the solid system.
[0014] Preferably, when the retarder is prepared, the mass ratio of the solid system to the deionized water is 1:3-4.
[0015] Preferably, in S11 to S13, the molar ratio of 2-acrylamide-2-methylpropane sulfonic acid, sodium 3-prop-2-enoyloxypropane-1-sulfonate, carboxylic acid monomer and acrylamide monomer is 6-7.5:0.5-2:1.5-2:2-2.5.
[0016] Preferably, nitrogen is introduced throughout the reaction process in S13 to isolate oxygen.
[0017] Preferably, the zinc source in S1 is one or more of zinc nitrate, zinc oxide, and zinc sulfate, and the aluminum source is one or more of polyaluminum chloride, aluminum sulfate, and aluminum nitrate.
[0018] Preferably, the molar ratio of zinc, aluminum, hydroxide and carbonate in S1 is 1-2:1:3-5:0.5-1.
[0019] Preferably, the zinc-aluminum hydrotalcite in S2 is calcined at 300-500° C. for 4-6 hours.
[0020] Preferably, the mass ratio of the admixture to the zinc-aluminum hydrotalcite in S3 is 3-10:1, the mixture is reacted at 25-40°C for 48-72h, naturally cooled and washed with water until neutral, and dried at 60°C.
[0021] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: The invention uses a zinc-aluminum hydrotalcite calcined product to add a retarder for adsorption to prepare an admixture for oil well cement with large temperature difference and high salt resistance. The zinc-aluminum hydrotalcite calcined product is prepared by preparing a zinc-aluminum hydrotalcite precursor with a zinc source and an aluminum source, and then calcining at a low temperature. The retarder is prepared by adding a chelating agent and an initiator to polymerize 2-acrylamide-2-methylpropane sulfonic acid, sodium 3-prop-2-enoyloxypropane-1-sulfonate, a carboxylic acid monomer, and an acrylamide monomer as raw materials. The invention has a simple preparation process and is easy to realize industrial production. The zinc-aluminum hydrotalcite is used as a carrier, and the porosity can be reduced in the early stage of oilfield cement hydration, the water seepage resistance can be enhanced, and the compressive strength of the cement can be improved. The chlorine atoms in the oilfield cement can be adsorbed, so that the admixture for large temperature difference and high salt resistance oil well cement has salt resistance, and the effective components can be slowly released at high temperature to further achieve a retarding effect. The invention can solve the problems of abnormal thickening of cement slurry in the early stage of hydration at high temperature caused by directly adding a retarder to the oilfield cement and excessive retarding caused by adding too much retarder, and is suitable for large temperature difference and high temperature environments.
[0022] The invention adopts zinc-aluminum hydrotalcite as a carrier, which can not only reduce the porosity and enhance the water seepage resistance in the early stage of oilfield cement hydration, but also absorb chloride ions in the solution and has high salt resistance. The calcination treatment makes the retarder adsorbed and embedded in the hydrotalcite calcination product, and the zinc oxide impurities formed by the calcination not only do not affect the rheology of the oilfield cement, but also the zinc hydroxide generated by the zinc oxide and water can form a film to inhibit the hydration reaction, and has a certain retarding effect.
[0023] The retarder of the present invention introduces a sulfonic acid group which is not easy to hydrolyze, has good temperature resistance and poor sensitivity to the attack of external metal cations, thereby improving the high temperature resistance and salt resistance of the retarder; the hydroxyl groups with strong hydrophilicity and adsorption capacity can construct a network structure on the surface of cement particles, thereby improving the filtration and water loss control ability of the retarder; and the long side chains contained have lubrication and steric hindrance effects, thereby improving the rheological properties of cement slurry.
[0024] The retarder produced by dehydration and decomposition of hydrotalcite at high temperature can continue to play a retarding effect and can respond to temperature intelligently, so that the admixture is suitable for large temperature difference and high temperature environment. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1: The preparation process of the admixture for large temperature difference and high salt resistance oil well cement of this embodiment comprises the following steps: S1. Add 8.1 g zinc oxide and 10.0 g polymerized aluminum oxide to a mixed solution of 12 g sodium hydroxide and 5.3 g sodium carbonate, adjust the solution pH to 9, and perform dynamic crystallization at 70° C. for 6 h to obtain a ZnAl-CO3-LDH precursor; S2, calcining 40 g of ZnAl-CO3-LDH precursor at 300° C. for 4 h to obtain a calcined zinc-aluminum hydrotalcite product; S3. Add 90g of retarder into deionized water, introduce ultrasonic dispersion under nitrogen, add 30g of calcined product of zinc-aluminum hydrotalcite into the retarder solution, react at 25°C for 48h, stir continuously during the reaction, and after the reaction is completed, cool naturally and wash with water until neutral, and dry at 60°C to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
[0027] The preparation method of the above-mentioned retarder is as follows: S11, add 113.4 g of 2-acrylamide-2-methylpropanesulfonic acid, 10.8 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate, and 19.5 g of itaconic acid into deionized water, stir at room temperature until the three monomers are completely dissolved, and then pour into a four-necked flask; S12, adding sodium hydroxide solution dropwise to the solution to adjust the pH value of the solution to 5, weighing 14.6 g of N,N-dimethylacrylamide and 1.8 g of ethylenediaminetetraacetic acid, stirring evenly and pouring into a four-necked flask; S13. When the temperature reaches 60°C, add 2.2 g of ammonium persulfate dropwise into the four-necked flask, introduce nitrogen, react at 60°C for 0.5 h, then raise the temperature to 70°C and react for 2.5 h. After the reaction is completed, collect and obtain the liquid retarder.
[0028] Example 2: The preparation process of the admixture for large temperature difference and high salt resistance oil well cement of this embodiment comprises the following steps: S1. Add 16.3 g zinc oxide and 10.0 g polymerized aluminum oxide to a mixed solution of 20 g sodium hydroxide and 10.6 g sodium carbonate, adjust the solution pH to 10, and perform dynamic crystallization at 90° C. for 10 h to obtain a ZnAl-CO3-LDH precursor; S2, calcining 40 g of ZnAl-CO3-LDH precursor at 500° C. for 6 h to obtain a calcined zinc-aluminum hydrotalcite product; S3. Add 300 g of retarder into deionized water, introduce nitrogen and perform ultrasonic dispersion, add 30 g of calcined zinc-aluminum hydrotalcite into the retarder solution and react at 40° C. for 72 h, stirring continuously during the reaction. After the reaction is completed, cool naturally and wash with water until neutral, and dry at 60° C. to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
[0029] The preparation method of the above-mentioned retarder is as follows: S11, add 141.7 g of 2-acrylamide-2-methylpropanesulfonic acid, 43 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate, and 26.0 g of itaconic acid into deionized water, stir at room temperature until the three monomers are completely dissolved, and then pour into a four-necked flask; S12, adding sodium hydroxide solution dropwise to the solution to adjust the pH value of the solution to 6, weighing 18.3 g of N,N-dimethylacrylamide and 2.8 g of ethylenediaminetetraacetic acid, stirring evenly and pouring into a four-necked flask; S13. When the temperature reaches 60°C, 3.7 g of ammonium persulfate is added dropwise to the four-necked flask, nitrogen is introduced, and the mixture is reacted at 65°C for 1 hour, and then the temperature is raised to 75°C for 3 hours. After the reaction is completed, the liquid retarder is collected.
[0030] Example 3, the preparation process of the admixture for large temperature difference and high salt resistance oil well cement of this embodiment comprises the following steps: S1. Add 12.2 g zinc oxide and 10.0 g polymerized aluminum oxide to a mixed solution of 18.0 g sodium hydroxide and 8.5 g sodium carbonate, adjust the solution pH to 9.5, and perform dynamic crystallization at 80° C. for 8 h to obtain a ZnAl-CO3-LDH precursor; S2, calcining 40 g of ZnAl-CO3-LDH precursor at 400° C. for 5 h to obtain a calcined zinc-aluminum hydrotalcite product; S3. Add 180g of retarder into deionized water, introduce nitrogen and disperse ultrasonically, add 30g of calcined zinc-aluminum hydrotalcite into the retarder solution and react at 30°C for 60h, stirring continuously during the reaction. After the reaction is completed, cool naturally and wash with water until neutral, and dry at 60°C to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
[0031] The preparation method of the above-mentioned retarder is as follows: S11, add 132.3 g of 2-acrylamide-2-methylpropanesulfonic acid, 21.6 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate, and 20.8 g of itaconic acid into deionized water, stir at room temperature until the three monomers are completely dissolved, and then pour into a four-necked flask; S12, add sodium hydroxide solution dropwise to the solution to adjust the pH value of the solution to 5.5, weigh 16.5 g of N,N-dimethylacrylamide and 1.9 g of ethylenediaminetetraacetic acid, stir well and pour into a four-necked flask; S13. When the temperature reaches 60°C, add 2.9 g of ammonium persulfate dropwise into the four-necked flask, introduce nitrogen, react at 60°C for 0.5 h, then raise the temperature to 70°C and react for 2.5 h. After the reaction is completed, collect and obtain the liquid retarder.
[0032] Example 4: The preparation process of the admixture for large temperature difference and high salt resistance oil well cement of this embodiment comprises the following steps: S1. Add 10.0 g zinc oxide and 10.0 g polymerized aluminum oxide to a mixed solution of 14.0 g sodium hydroxide and 7.5 g sodium carbonate, adjust the solution pH to 9, and perform dynamic crystallization at 90° C. for 6 h to obtain a ZnAl-CO3-LDH precursor; S2, calcining 40 g of ZnAl-CO3-LDH precursor at 500° C. for 4 h to obtain a calcined zinc-aluminum hydrotalcite product; S3. Add 120g of retarder into deionized water, introduce nitrogen and disperse ultrasonically, add 30g of calcined zinc-aluminum hydrotalcite into the retarder solution and react at 30°C for 72h, stirring continuously during the reaction. After the reaction is completed, cool naturally and wash with water until neutral, and dry at 60°C to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
[0033] The preparation method of the above-mentioned retarder is as follows: S11, add 122.9 g of 2-acrylamide-2-methylpropanesulfonic acid, 32.4 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate, and 24.7 g of itaconic acid into deionized water, stir at room temperature until the three monomers are completely dissolved, and then pour into a four-necked flask; S12, adding sodium hydroxide solution dropwise to the solution to adjust the pH value of the solution to 5.5, weighing 16.5 g of N,N-dimethylacrylamide and 2.1 g of ethylenediaminetetraacetic acid, stirring evenly and pouring into a four-necked flask; S13. When the temperature reaches 60°C, add 2.6 g of azobisisobutyronitrile dropwise into the four-necked flask, introduce nitrogen, react at 60°C for 0.5 h, then raise the temperature to 70°C and react for 2.5 h. After the reaction is completed, collect and obtain the liquid retarder.
[0034] Example 5, the preparation process of the admixture for large temperature difference and high salt resistance oil well cement of this embodiment comprises the following steps: S1. Add 14.5 g zinc oxide and 10.0 g polymerized aluminum oxide to a mixed solution of 19.0 g sodium hydroxide and 5.3 g sodium carbonate, adjust the solution pH to 10, and perform dynamic crystallization at 70° C. for 10 h to obtain a ZnAl-CO3-LDH precursor; S2, calcining 40 g of ZnAl-CO3-LDH precursor at 300° C. for 6 h to obtain a calcined zinc-aluminum hydrotalcite product; S3. Add 150g of retarder into deionized water, introduce nitrogen and disperse ultrasonically, add 30g of calcined zinc-aluminum hydrotalcite into the retarder solution and react at 25°C for 48h, stirring continuously during the reaction. After the reaction is completed, cool naturally and wash with water until neutral, and dry at 60°C to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
[0035] The preparation method of the above-mentioned retarder is as follows: S11, add 141.7 g of 2-acrylamide-2-methylpropanesulfonic acid, 27.0 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate, and 23.4 g of itaconic acid into deionized water, stir at room temperature until the three monomers are completely dissolved, and then pour into a four-necked flask; S12, adding sodium hydroxide solution dropwise to the solution to adjust the pH value of the solution to 5, weighing 20.1 g of N,N-dimethylacrylamide and 1.8 g of sodium pyrophosphate, stirring evenly and pouring into a four-necked flask; S13. When the temperature reaches 60°C, add 2.5 g of ammonium persulfate into the four-necked flask, introduce nitrogen, react at 60°C for 0.5 h, then raise the temperature to 70°C and react for 2.5 h. After the reaction is completed, collect and obtain the liquid retarder.
[0036] Example 6: The preparation process of the admixture for large temperature difference and high salt resistance oil well cement of this embodiment comprises the following steps: S1. Add 15.0 g zinc oxide and 10.0 g polymerized aluminum oxide to a mixed solution of 16.0 g sodium hydroxide and 5.3 g sodium carbonate, adjust the solution pH to 10, and perform dynamic crystallization at 90° C. for 9 h to obtain a ZnAl-CO3-LDH precursor; S2, calcining 40 g of ZnAl-CO3-LDH precursor at 300° C. for 6 h to obtain a calcined zinc-aluminum hydrotalcite product; S3. Add 270g of retarder into deionized water, introduce nitrogen and disperse ultrasonically, add 30g of calcined zinc-aluminum hydrotalcite into the retarder solution and react at 30°C for 72h, stirring continuously during the reaction. After the reaction is completed, cool naturally and wash with water until neutral, and dry at 60°C to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
[0037] The preparation method of the above-mentioned retarder is as follows: S11, add 137.0 g of 2-acrylamide-2-methylpropanesulfonic acid, 25.9 g of sodium 3-prop-2-enoyloxypropane-1-sulfonate, and 21.4 g of itaconic acid into deionized water, stir at room temperature until the three monomers are completely dissolved, and then pour into a four-necked flask; S12, adding sodium hydroxide solution dropwise to the solution to adjust the pH value of the solution to 5.5, weighing 18.0 g of N, N-dimethylacrylamide and 2.1 g of sodium pyrophosphate, stirring evenly and pouring into a four-necked flask; S13. When the temperature reaches 60°C, add 3.1 g of ammonium persulfate dropwise into the four-necked flask, introduce nitrogen, react at 60°C for 0.5 h, then raise the temperature to 70°C and react for 2.5 h. After the reaction is completed, collect and obtain the liquid retarder.
[0038] Comparative Example 1: The difference between this comparative example and Example 1 is that the molar ratio of zinc, aluminum, hydroxide and carbonate is changed to 3:1:6:1, and the calcination conditions for the zinc-aluminum hydrotalcite calcined product are changed to calcination at 900°C for 6h.
[0039] Comparative Example 2: This comparative example differs from Example 1 in that the carboxylic acid monomer for preparing the retarder is changed to acrylic acid, and sodium 3-prop-2-enoyloxypropane-1-sulfonate is changed to sodium methacrylic acid.
[0040] Performance test of admixtures for large temperature difference and high salt resistance oil well cement The cement slurry was prepared according to GB / T19139-2012 "Test Methods for Oil Well Cement". The cement formula is shown in Table 1: Table 1 Cement formula
[0041] Salt resistance test The admixtures prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were added to the cement slurry systems of semi-saturated brine and saturated brine, and the static API water loss of the cement slurry systems of semi-saturated brine and saturated brine was tested. The prepared cement slurry was placed in a normal pressure thickener for curing for 20 minutes and then poured into a high temperature and high pressure water loss instrument to collect the water loss of the cement slurry within 30 minutes. The test temperature was 220°C and the test pressure was 6.9 to 7.1 MPa. The static API water loss calculation formula of the cement slurry is as follows:
[0042] Where V API It is the static API water loss of cement slurry, in mL.
[0043] V t It is the volume of cement slurry water loss collected within 30 minutes, in mL.
[0044] T is the time for collecting cement slurry filtration water loss, in minutes.
[0045] The test results are shown in Table 2: Table 2 Static API water loss test of cement slurry system with semi-saturated brine and saturated brine
[0046] It can be seen from the data in Table 2 that the static API water loss of the cement slurries of Examples 1 to 6 in semi-saturated brine and saturated brine is all below 50 mL, meeting the static API water loss requirement of oilfield cement, and the static API water loss in semi-saturated brine and saturated brine does not change much, indicating that the admixture prepared by the present invention has excellent salt resistance.
[0047] The static API water loss of the cement slurry in comparative example 1 in semi-saturated salt water is less than 50mL, but the static API water loss in saturated salt water is greater than 50mL. The reason is that the raw material ratio and calcination conditions for preparing zinc-aluminum hydrotalcite do not meet the requirements, resulting in changes in the structure of zinc-aluminum hydrotalcite, and the amount of adsorbed effective components of the retarder is greatly reduced. In semi-saturated salt water, zinc-aluminum hydrotalcite and a small amount of retarder in the admixture can exert a certain salt resistance, but in saturated salt water, due to too few effective components of the admixture and changes in the structure of zinc-aluminum hydrotalcite, the ability to adsorb chloride ions is greatly reduced, and the salt resistance performance does not meet the requirements. The static API water loss in semi-saturated salt water of comparative example 2 is close to 50mL, and the static API water loss in saturated salt water is greater than 50mL. The reason is that the ingredients for preparing the retarder are changed, and the carboxylic acid monomer is changed to acrylic acid. The retarder cannot construct a network structure on the surface of the cement particles through the carboxyl group, which reduces the retarder's ability to control filtration and water loss, thereby affecting the salt resistance of the admixture, resulting in the static API water loss of the cement slurry in saturated salt water not meeting the requirements.
[0048] Large temperature difference slow setting test The admixtures prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were added to cement slurry and thickened at 140°C, 160°C, 180°C and 200°C. The time from the start of the reaction until the cement slurry reached a consistency of 70 Bc was recorded. The test results are shown in Table 3: Table 3 Cement slurry thickening time test
[0049] It can be seen from the data in Table 3 that as the thickening temperature increases, the thickening time of the cement slurry is shortened. After the admixtures prepared in Examples 1 to 6 are added to the cement slurry, the thickening time at 140 to 200°C is more than 200 minutes, and as the temperature increases, the thickening time of the cement slurry does not decrease significantly, indicating that the admixture prepared by the present invention has excellent retarding ability at high temperatures, and at a temperature difference of 60°C, the retarding effect of the admixture is not lost, indicating that the admixture prepared by the present invention is suitable for environments with large temperature differences and high temperatures.
[0050] The thickening time of the cement slurry in Comparative Example 1 is reduced compared with the thickening time of Examples 1 to 6, and the thickening time at 200°C is significantly reduced. The reason is that the raw material ratio and calcination conditions for preparing zinc-aluminum hydrotalcite do not meet the requirements, resulting in changes in the structure of zinc-aluminum hydrotalcite, which cannot respond intelligently to changes in ambient temperature, causing the effective ingredients of the retarder in the admixture to be released prematurely at high temperatures. Since the concentration of free calcium ions in the solution in the early stage of cement hydration under high temperature conditions is relatively low, the retarder molecules compete for calcium ions and multiple retarder molecules chelate one calcium ion, thereby causing the high molecular long-chain polymer to form a bridge network, resulting in non-chelated retarder molecules being entrained in the bridge network polymer, so that the hydration process of the cement slurry cannot be effectively inhibited, resulting in a decrease in the cement thickening time, which cannot meet the needs of cement in oil fields with large temperature differences. The thickening time of the cement slurry in Comparative Example 2 is also significantly shortened compared with the thickening time of Examples 1 to 6. The reason is that the composition of the retarder is changed, resulting in the lack of long side chains and carboxyl groups in the retarder molecules, which makes the retarder molecules lack lubrication and steric hindrance, and cannot effectively improve the rheological properties of the cement slurry, thereby affecting the shortening of the thickening time of the cement.
[0051] Large temperature difference compressive strength test The admixtures prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were added to cement slurry as the experimental group, and the cement slurry without admixture was used as the control group. The prepared cement slurry was placed in a high temperature and high pressure thickener, heated to the cycle temperature and maintained for 1 hour, and then the cement slurry was taken out after cooling, and placed in a mold and cured in a 60°C water bath for 3 days before being taken out for compressive strength testing. The cycle temperature was set at 120°C, 180°C, and 240°C. The compressive strength of cement was calculated as follows:
[0052] Where P is the compressive strength, in MPa.
[0053] F is the maximum pressure in kN.
[0054] L is the length of cement stone, in meters.
[0055] The test results are shown in Table 4: Table 4 Cement compressive strength test
[0056] It can be seen from the data in Table 4 that after the cement slurry solidifies into cement paste, the compressive strength of the cement paste at 3d decreases with the increase of the cycle temperature. The compressive strength of the cement slurries of Examples 1 to 6 at 3d decreases less, and the compressive strength is higher than that of the control group without the addition of the admixture, indicating that the addition of the admixture prepared by the present invention can significantly improve the early compressive strength of the cement paste at a temperature difference of 60 to 180°C.
[0057] Compared with the experimental group, the compressive strength of cement paste in Comparative Examples 1 and 2 at 3d is improved, but the improvement is lower than that in Examples 1 to 6. The reason is that the structure of the zinc-aluminum hydrotalcite in Comparative Example 1 changes, resulting in a decrease in its adsorption capacity, and the increase in the early compressive strength of the cement is lower than that in the examples. The composition of the retarder prepared in Comparative Example 2 is changed, resulting in the lack of long side chains and carboxyl groups in the retarder molecules, which reduces the water loss control ability and rheological capacity of the cement slurry added thereto, thereby making the early compressive strength of the cement lower than the early compressive strength of the cement in the examples.
[0058] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0059] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for preparing an admixture for large temperature difference and high salt resistance oil well cement, characterized in that: The following steps are involved: S1, adding zinc source and aluminum source to a mixed solution of sodium hydroxide and sodium carbonate, adjusting the solution pH to 9.5±0.5, and dynamically crystallizing at 70~90°C for 6~10h to obtain a ZnAl-CO3-LDH precursor; S2, calcining the ZnAl-CO3-LDH precursor at low temperature to obtain a zinc-aluminum hydrotalcite calcined product; S3. Add the retarder into deionized water, introduce nitrogen and disperse ultrasonically, add the calcined product of zinc-aluminum hydrotalcite into the retarder solution for reaction, stir continuously during the reaction, and after the reaction is completed, cool naturally and wash with water until neutral, and dry at 60°C to obtain an admixture for oil well cement with large temperature difference and high salt resistance.
2. The preparation process of the admixture for large temperature difference and high salt resistance oil well cement according to claim 1, characterized in that: The preparation method of the retarder comprises the following steps: S11, adding 2-acrylamide-2-methylpropanesulfonic acid, sodium 3-prop-2-enoyloxypropane-1-sulfonate, and carboxylic acid monomers into deionized water, stirring at room temperature until the three monomers are completely dissolved, and then pouring into a four-necked flask; S12, adding sodium hydroxide solution dropwise to the solution, adjusting the pH value of the solution to 5-6, adding acrylamide monomer and chelating agent, stirring evenly and pouring into a four-necked flask; S13, when the temperature reaches 60°C, add an initiator dropwise into the four-necked flask, react at 60-65°C for 0.5-1h, then raise the temperature to 70-75°C for 2.5-3h, and collect the liquid retarder after the reaction is completed; The solid system comprises 2-acrylamide-2-methylpropane sulfonic acid, sodium 3-prop-2-enoyloxypropane-1-sulfonate, carboxylic acid monomers, acrylamide monomers, a chelating agent and an initiator.
3. The preparation process of the admixture for large temperature difference and high salt resistance oil well cement according to claim 2, characterized in that: The carboxylic acid monomer in S11 is one or more of itaconic acid, acrylic acid, maleic anhydride, and cis-2-methyl-2-butenedioic acid.
4. The preparation process of the admixture for large temperature difference and high salt resistance oil well cement according to claim 2, characterized in that: In the S12, the acrylamide monomer is one or more of N,N-dimethylacrylamide and acrylamide, the chelating agent is one or more of ethylenediaminetetraacetic acid and sodium pyrophosphate, and the added mass of the chelating agent is 0.24-0.3% of the total mass of the added solid and water.
5. The preparation process of the admixture for large temperature difference and high salt resistance oil well cement according to claim 2, characterized in that: The initiator in S13 is one or more of ammonium persulfate and azobisisobutyronitrile, and the amount of initiator added is 1.4-1.6% of the mass of the solid system. Nitrogen needs to be introduced throughout the reaction process to isolate oxygen.
6. The preparation process of the admixture for large temperature difference and high salt resistance oil well cement according to claim 2, characterized in that: When the retarder is prepared, the mass ratio of the solid system to deionized water is 1:3-4, and the molar ratio of 2-acrylamide-2-methylpropane sulfonic acid, sodium 3-prop-2-enoyloxypropane-1-sulfonate, carboxylic acid monomer and acrylamide monomer is 6-7.5:0.5-2:1.5-2:2-2.
5.
7. The preparation process of the admixture for large temperature difference and high salt resistance oil well cement according to claim 1, characterized in that: The zinc source in S1 is one or more of zinc nitrate, zinc oxide, and zinc sulfate, the aluminum source is one or more of polyaluminum chloride, aluminum sulfate, and aluminum nitrate, and the molar ratio of zinc, aluminum, hydroxide, and carbonate is 1-2:1:3-5:0.5-1.
8. The process for preparing the admixture for large temperature difference and high salt resistance oil well cement according to claim 1, characterized in that: The zinc-aluminum hydrotalcite in S2 is calcined at 300-500° C. for 4-6 hours.
9. The process for preparing the admixture for large temperature difference and high salt resistance oil well cement according to claim 1, characterized in that: The mass ratio of the admixture to the zinc-aluminum hydrotalcite in S3 is 3-10:1, and the mixture is reacted at 25-40°C for 48-72h, naturally cooled and washed with water until neutral, and dried at 60°C.
Citation Information
Patent Citations
Water soluble amphoteric hydrophobic polymer set retarder and preparation method and application thereof
CN105399898A
Seawater well cementing slow release type fluid loss additive and preparation method and application thereof
CN107502313A
Weak-dispersion early-strength retarder for oil well cement and preparation method thereof
CN114057958A
Multi-slag solid alkaline cement and preparation method thereof
CN114507043A
Cement composition
JP1998279343A
Cited By
White belite sulphoaluminate cementing material and preparation method thereof
CN120887694A